Engaging Millennial Students in Leadership Education - Jill R. Arensdorf; Anthony C. Andenoro (Educational Considerations, 2009)
As new generations of young people mature and enter higher education, educators must adapt their teaching methodologies through an examination of theory and research related to generational differences.
Keywords: Millennial; undergraduate; practices; Experiential learning; leadership; philosophy; theories; concepts; education; expectations